Laparoscopic management of ectopic pregnancy: a 34-month retrospective study at Amath Dansokho Regional Hospital Center, Kédougou, Senegal - Mouhamadou, Wade; Alfred Ndiaye, Sarr; Alexandre Oumar, Seck; Fallou, Diouf; Yababba Moussa Gambo, Aminatou; Nogaye, Gueye; Doudou, Sané (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Ectopic pregnancy (EP) is a major gynecological emergency with significant incidence in rural settings where access to care is limited. Laparoscopic surgery is now recognized as the reference technique for EP treatment. This study reports the experience of the Amath Dansokho Regional Hospital Center of Kédougou in the laparoscopic management of EP. Methods: A retrospective descriptive study was conducted on 30 patients operated by laparoscopy for EP between September 2022 and July 2025 at Amath Dansokho Regional Hospital Center, a rural level II hospital located 800 km from Dakar. Sociodemographic, clinical, surgical data and postoperative outcomes were analyzed. Results: The mean age of patients was 26.3 years. The majority of EPs were located on the left fallopian tube (53.3%) and ruptured in 70% of cases. The laparoscopic management rate for EP was 71.4%. Anterograde salpingectomy was the main procedure in 80% of interventions. Postoperative outcomes were favourable with no conversion to laparotomy and an average hospital stay of 2 days. Conclusions: Laparoscopy is a safe and effective technique for managing EP in rural settings, reducing morbidity and hospital stay. Its development in resource-limited areas requires capacity building and adequate training of medical teams.